Characterization of Five Microsatellite Markers For Genetic Diversity Structure Analysis of Walnut (Juglans Regia L) in Five Village in Duhok Province - Barwary, Awat M.A. (Science Journal of University of Zakho, 2015)
Five microsatellites markers (WGA202, WGA009, WGA332, WGA225 and WGA069) were used to characterize Persian walnuts (Juglans regia L.) populations in five villages (Sharanesh, Bedohe, Kanizarke (Akre), Kashane and Kuzo) of Duhok province. The microsatellites amplified (PCR products) a total of 186 alleles across all populations. The number of alleles per locus ranged from 4 alleles in Sharanesh and Kashane populations to 10 alleles also in Sharanesh and Kashane populations, with an average of 7.4. The molecular sizes of the amplified bands ranged from 158 bp to 289 bp in all populations. The observed heterozygosity (Ho) within populations ranged from 0.59 at WGA225 to 0.65 in the locus WGA202 with an average of 0.61. The PIC value (0.88) indicated that all markers were highly informative and useful for genetic diversity studies in these populations. The proportion of genetic variation presented among populations accounted for 8.4% of the total genetic diversity so it indicated a moderate level of genetic diversity between populations. The Fis average 0.24 indicated that, there was a regular tendency toward heterozygote deficiency and indicated the presence of inbreeding within the populations. The phylogenetic analysis or unrooted neighbor-joining tree highlighted the genetic distance among those five populations and separated them into two main groups placing each population according to its genetic background. The first group consists of populations Bedohe and Sharanesh in one subgroup and Kashane in second subgroup. The second group consists of populations Akre and Kuzo.